User and healthcare provider early experiences with the PrEP ring: a quantitative study on the introduction of a new PrEP method in Eswatini - Anita Hettema; Siphesihle Shongwe; Haley Sisel; Mxolisi Khumalo; Ncediso Gama; Nolwazi Khanyile; Buyile Mahlalela; Sindy Nana Matse; Jill M. Peterson (Journal of the International AIDS Society, 2025)
Abstract Introduction Eswatini prepared for the national rollout of HIV pre‐exposure prophylaxis (PrEP) choice through a mixed‐method demonstration study introducing the PrEP dapivirine vaginal ring in 12 Ministry of Health‐supported sites. The Eswatini PrEP Ring Study aimed to describe user preferences for, and experiences with, the PrEP ring, and provider impressions. The objective was to provide real‐world data on client preferences and experiences related to PrEP choice, and healthcare provider perspectives on the feasibility and acceptability of offering PrEP choice. A subset of quantitative findings is presented here. Methods During May 2023–August 2024, 12 study sites in Eswatini began offering a choice between the PrEP ring and oral PrEP to women 18 years and older who were HIV negative, not pregnant or breastfeeding, and interested in PrEP. Current oral PrEP users who were satisfied with the method were not recruited. Users’ early experiences with the PrEP ring were assessed through structured enrolment and follow‐up questionnaires. Factors associated with choosing the PrEP ring at enrolment were assessed using logistic regression. During the first 2 months of offering PrEP choice, providers (n = 16) completed a structured questionnaire on the feasibility and acceptability of PrEP choice service delivery. Clinical Trial Number: NCT05889533 Results At enrolment, 69% (n = 625/904) chose the PrEP ring. Predictors for choosing the ring included ages 25+ (25–34 years AOR = 1.44, 95% CI [1.03, 2.02]; ages 35+ years AOR = 1.69, 95% CI [1.07, 2.68]), higher education (AOR = 1.71 for some/completed high school, 95% CI [1.20, 2.43]; AOR = 1.87 for vocational/tertiary education, 95% CI [1.21, 2.90]) and using either longer‐acting (AOR = 2.23, 95% CI [1.28, 3.89]) or shorter‐acting contraceptives (AOR = 1.63, 95% CI [1.14, 2.32]) versus no modern family planning method. Participants reported high levels of ease and confidence (98%) in using the ring. Ninety‐four percent of PrEP counsellors (n = 8) and nurses (n = 8) felt prepared to offer PrEP choice and liked choice counselling but had concerns about clients’ ability to return on time for refills of either method. Conclusions Many women in Eswatini were willing to try the PrEP ring. Providers were enthusiastic about counselling on PrEP choice and introducing women to the ring.